Haplotype Diversity in the Mitochondrial COI Gene of Barred Rainbowfish (Chilaterina fasciata) from Mamberamo River of Western New Guinea, Indonesia - Widya Pintaka Bayu Putra; Arif Wibowo; Anang Hari Kristanto (Bogor Agricultural University, Indonesia, 2024)
A Barred rainbowfish (Chilatherina fasciata) is one of the native fish species found in Western New Guinea of Indonesia. This study aimed to observe the levels of haplotype diversity in the partial Cytochrome-c oxidase subunit I (COI) gene of Barred rainbowfish. For the DNA analysis, thirty (30) Barred rainbowfishes were caught from the Mamberamo River. Three (3) molecular packages of BioEdit, MEGA, and DNAsp were used to analyze twenty (30) forward sequences of the COI gene (502 bp). The research showed four (4) haplotypes for the examined population, a total of seven (7) mutations, and low genetic diversity detected in the partial COI gene with the haplotype diversity (Hd) = 0.405 and nucleotide diversity (pi) = 0.003. Meanwhile, the Fu's and Tajima's tests were 1.21 and -0.69, respectively. The UPGMA tree with 1,000 × bootstrap replications revealed that Barred rainbowfishes are grouped into similar clusters with Melanotaenia vanheurni, Chilatherina alleni, and Chilatherina bleheri. In conclusion, haplotype 3 (77%) was detected as the common haplotype for Barred rainbowfishes at the Mamberamo River of Western New Guinea.